Avaliação da atividade antimutagênica e citotóxica dos venenos de Rhinella marina e Rhaebo guttatus - Oliveira, Angellica Fernandes de (2017)
Bufonidae toads have bufadienolides with biological activities in the treatment of cardiac pathologies, pain and cancer. Although toxic effects, venom have a high potential for the production of new medicine. The propused sutudy had the objective to evaluate the antimutagenic and cytotoxic activity of Rhinella marina and Rhaebo guttatus venom through in vitro and in vivo assays. In vitro and in vivo assays, as well as biochemical analysis of the serum enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST) and creatinine (CRT) for hepatic and renal damage respectively. For the evaluation of cytotoxic activity in vitro was used the colorimetric method based on MTT (3- [4,5-dimethyl-2- thiazolyl] -2,5-diphenyl-2H-tetrazolium bromide) the extracts were made in the concentrations of 7.81; 15.62; 31.25; 62.5 and 125 μg / ml and were added to cultures with Walker 256 Tumor cells or splenic cells from Swiss mouse and rat. For the in vivo assay the micronucleus test was performed on bone marrow cells of Swiss male mice (7 animals / group), and the treated groups received for 15 consecutive days, via oral gavage, the extract of R. marina and R. guttatus at a dose of 7 μg / mL. On the 15th day they received an intraperitoneal injection of N-ethyl-N-nitrosurea (ENU, 50 mg / Kg), being sacrificed 24 hours after the treatment to evaluate the frequency of micronucleated polychromatic erythrocytes (PCEMNs). The extracts of R. marina and R. guttatus presented cytotoxic action for rat and Swiss mouse splenic cells and for Walker 256 Tumor. In the micronucleus test it was observed an antimutagenic activity of venom extracts with a significant reduction in the frequency of PCEMNs in relation to the positive control group (R. marina = 56% and R. guttatus = 75%, p <0.001). At the same time, the groups treated only with the extracts presented an increase in the frequency of PCEMNs when compared to the negative control, with a significant difference (p <0.01), which exposes a mutagenic potential of the venom. In the biochemical analyzes of serum AST, ALT and CRT, no significant difference was observed between treatments (p> 0.05). Analyzing the results obtained, the extracts of R. marina and R. guttatus presented cytotoxic, antimutagenic and mutagenic activities, but no hepatic and renal changes were observed under the conditions that the experiment was realized.